The Role of the Strategic Leadership Approach in the Management of Institutions and its Relationship to Profitability - Abdulaziz Abdulrahman Boshi (Scholars Digest Publishing, 2023)
Today's competitive environment is rapidly changing, thus most CEOs work to implement flexible procedure techniques such like strategic leadership to ensure that their companies can also change. This technique can be used by strategic leaders to inspire unity and cooperation among their teams so that they can create a positive impact on the organization as a whole but the significance of strategic leadership and its influence on large-scale profitability is not recent. So, it is essential to study the role of this type of leadership in the management and productivity or profitability of an organization and highlights the issues encountered through its implementation. This paper investigates the effect of strategic leadership on decision-making and organizational profitability and states some solutions to the obstacles which affect strategic leadership execution. Questionnaire surveys were employed to gather information. The respondents are varied between managers, chief officers, human resource employees, and others. The questionnaire also targets various sizes of companies. After collecting the data, the SPSS program was relied on to conduct the necessary tests to demonstrate the validity of the null and alternative hypotheses. The findings concluded that strategic leadership has an effective role in improving job performance and thus ensuring profitability. Also, there are many obstacles facing the achievement of strategic leadership in the organization such like: limited financial and human resources, lack of preparation while implementing the strategy, political interference, and late funding. The author recommends some solutions that are useful in overcoming those obstacles facing the strategic leadership, including: supporting cooperation and coordination between different directors, recommending communication strategy, bureaucracy eliminate, recommending proper planning, and raising staff morale.
Keywords: Strategic Leadership; Organizational Profitability; Decision-making.